Impact of late shift Rapid Response Team (RRT) input on length of stay and discharge destination in emergency care - Mahender Yennaram; Hayley R; Rebecca D; Vikram M (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Prolonged length of stay (LOS) is a significant financial burden to the hospitals. Although Physiotherapists (PT) are expanding their role in different areas of health care, including Emergency Care (EC), the impact of late shift PT input on LOS is not yet known. The objective was to determine the impact of the late shift Rapid Response Team (RRT) input on LOS and discharge destination. Patients who are referred to the RRT Physiotherapy/Occupational Therapy (PT/OT) include those with musculoskeletal conditions, cardio-respiratory and neurological problems. The therapists establish patient’s premorbid mobility level, social status and complete mobility and balance assessments. The outcome measures considered for this study was LOS and discharge destination. A total of 131 patients were assessed during 2016/2017. Out of 131, 72 patients were discharged on the day of treatment. Out of 138 patients referred during 2017/2018, 79 patients were discharged on the day of assessment. Most patients had significant comorbidities when admitted as the number of comorbidities is approximately four conditions for both durations. The discharge destination included from patients own home, rehabilitation hospital, long stay wardand interim placementfrom ward and this has saved 151 bed days in the hospital. Late shift RRT service in the ED resulted in reduced LOS and improved discharge destination.